Peru’s 2030 National Development Plan for the cacao and chocolate value chains (Plan Nacional de Desarrollo de la Cadena de Cacao y Chocolate al 2030) incorporates zero deforestation criteria - CGIAR Research Program on Water, Land and Ecosystems (2021)
Peru's 2030 National Development Plan has incorporated zero deforestation criteria recommended by WLE for its cacao and chocolate value chains